ETMR-09.In vitro modelling of embryonal tumors with multilayered rosettes (ETMR) and other novel brain tumor types. (3rd June 2022) - Bunt, Jens; Roosen, Mieke; Stathi, Phylicia; Polychronopoulos, Panagiotis; Odé, Zelda; Maas, Joris; Kool, Marcel
Abstract: Over the last decade, molecular characterization has resulted in many tumors previously classified as central nervous system primitive neuroectodermal tumors (CNS-PNETs) now being classified into their own distinct tumor types. These novel types are often characterized by very specific genomic aberrations. For instance, embryonal tumors with multilayered rosettes (ETMR) harbor amplifications of miRNA cluster C19MC or complex DICER1 mutations, while in CNS neuroblastoma with FOXR2 activation structural aberrations result in aberrant FOXR2 expression. Despite the presence of distinct oncodrivers, our understanding of these tumors is still limited. To elucidate tumor biology and to discover tumor specific treatments, we need to uncover how these oncodrivers contribute to tumorigenesis. However, a bottleneck in basic and translational research of these novel tumor types, is the lack of representative preclinical models, especially in vitro. To overcome this hurdle, we aim to mimic tumor development in genetically modified brain organoids. Human brain organoids derived from pluripotent stem cells are generated to represent either the developing forebrain or cerebellum. To mimic oncodriving events, DNA plasmids are introduced via electroporation into the proposed cell-of-origin populations to knockout tumor suppressor genes or overexpress oncogenes. By detecting fluorescent proteins encoded by the plasmids, electroporated cells are followed over time. Based on our preliminary data, for instance, overexpression of C19MC results in ectopic expansion of the electroporated cells. Ongoing histological and molecular characterizations, including (single cell) transcriptomic and epigenomic analyses, will reveal to which extend these organoid models resemble the specific human tumor types. Although further validation is required, these organoid models provide a novel avenue to study especially brain tumor types with distinct oncodriving events for which patient-derived models have not yet been established. They also allow for in-depth analyses of the potential cells of origin and the contribution of different mutations to tumor biology.